A Robust Cover Generation Technique for Steganography Using 2D Images - Ahmad Zawawi, Md. Nabil (2006)
Steganography is still in its infancy as in comparison to cryptography in terms of research and development. The word steganography comes from the Greek roots Steganos Graphos, that literary means ‘covered writing’. While cryptography aims to obstruct information access to unintended third party, the aim of steganography is to deny the very existence of it. Users of steganography do not advertise the existence of information in fact, denies its existence in the first place. Cryptography can be used prior to using steganography for an added layer of data security. The general model for steganography consists of three main components, that is the embedded data (the message one wishes to secretly send), the CoverObject (the media being used to hide the data) and the StegoObject (the product of using coverobject to hide the embedded data). Simmons (1984) introduces the Prisoners’ Problem as a classic scenario for covert communication. The problem describes a scenario where two prisoners named Alice and Bob that are put in two different cells and needed to communicate an escape plan with each other. All communications need to go through the warden, Willy and as long as Willy does not suspect anything, the communication can be put through. Many steganographic techniques mainly focus on the information payload and undetectability of the system. In this research, we approach the steganographic problem of a passive warden and also with great considerations the threats of an active attack by an active warden in which the robustness of the stegoobject is concerned. We see this third criteria as equally important as the first and second because an active attack does not require the attacker to know whether an object is a stegoobject or not. An active attack simply change or modify a particular object’s characteristic in its path with conditions that the object is still viewable and acceptable for general view. Applying the cover generation technique, the proposed steganographic technique can evade detection, able to carry useful amount of information and also at the same time survives an active attack that can jeopardise the information it carries.